2015
DOI: 10.1007/s11295-015-0871-0
|View full text |Cite
|
Sign up to set email alerts
|

Diverse chitinases are invoked during the activity-dormancy transition in spruce

Abstract: North temperate tree species such as white spruce (Picea glauca [Moench] Voss) have evolved strategies to protect themselves against abiotic and biotic stresses that trees encounter during the inclement winter months. Chitinases not only play well-documented roles in plant defense but also function during physiological and developmental preparations for overwintering, including growth cessation, cold and desiccation acclimation, and dormancy acquisition. Phylogenetic analysis of 31 white spruce and 52 Norway s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…Changes in cell wall structure and components are critical for the processes of growth and stress resistance (Zwiazek, 1991), and previous studies have shown the increase of cell wall formation and reactive oxygen species (ROS) signaling (Jian et al, 1997;Considine and Foyer, 2014) during bud dormancy. Chitinases were reported to be associated with protection against freezing and promote cell wall biosynthesis during dormancy in white spruce (González et al, 2015).…”
Section: Transcriptome Profiles Clustered By Bud Developmental Stagesmentioning
confidence: 99%
“…Changes in cell wall structure and components are critical for the processes of growth and stress resistance (Zwiazek, 1991), and previous studies have shown the increase of cell wall formation and reactive oxygen species (ROS) signaling (Jian et al, 1997;Considine and Foyer, 2014) during bud dormancy. Chitinases were reported to be associated with protection against freezing and promote cell wall biosynthesis during dormancy in white spruce (González et al, 2015).…”
Section: Transcriptome Profiles Clustered By Bud Developmental Stagesmentioning
confidence: 99%
“…Seasonal up-regulation of a dehydrin gene in bark tissue is lower and restricted to a shorter period in the evergrowing ( evg ) mutant of peach having a deletion in DAM genes, in concordance with its lower cold tolerance ( Arora et al, 1992 ; Arora and Wisniewski, 1994 ; Artlip et al, 1997 ). Diverse chitinases have been also suggested to act as antifreeze, storage, and defense proteins induced during the transition to dormancy in spruce ( González et al, 2015 ).…”
Section: Dormancy Setupmentioning
confidence: 99%
“…Previously, a class I chitinase was induced by low temperature in mature white spruce somatic embryos (Gao et al, 2022), but was suppressed by wounding (Hietala et al, 2004). Chitinases of different classes were also differentially expressed in P. glauca during the transition between seasonal activity and dormancy (González et al, 2015).…”
Section: Discussionmentioning
confidence: 99%